Molecular Epidemiology and Drug Resistant Mechanism of Carbapenem-Resistant Klebsiella pneumoniae in Elderly Patients With Lower Respiratory Tract Infection - Shao, Chunhong; Wang, Wei; Liu, Shuang; Zhang, Zhijun; Jiang, Meijie; Zhang, Fusen (Frontiers in Public Health, 2021)
Infection by carbapenem-resistant Klebsiella pneumoniae (CRKp) hampers the treatment of elderly patients with lower respiratory tract infection (LRTI); however, relevant data with respect to the characteristics of CRKp in elderly patients with LRTIs are limited. In the present study, K. pneumoniae isolated from elderly patients with LRTIs was collected and identified by VITEK-MS. VITEK 2 compact was used for drug sensitivity test to screen CRKps, and broth dilution method was used for drug sensitivity of tigecycline and colistin. The resistance genes, virulence genes, and serotypes of CRKps were detected via polymerase chain reaction. The homology of CRKps was analyzed via PFGE and MLST. Moreover, plasmid conjugation experiment was carried out to determine the transferability of carbapenem resistance. PCR-based replicon typing (PBRT) and S1 nuclease-PFGE were conducted for plasmid profiling. From January 2019 to August 2019, 258 elderly patients with LRTIs caused by K. pneumoniae were observed; of these, 31 (12.02%) infections were caused by CRKp strains. Majority of the patients were admitted to the intensive care unit and neurosurgery wards. Intracranial hemorrhage and pneumonia were the most common underlying diseases. Furthermore, 29 patients infected by CRKp had been exposed to various antimicrobial drugs before the positive culture. All isolates exhibited high resistance to β-lactam antibiotics. The predominant carbapenem resistance gene was blaKPC−2, and CRKps carrying blaKPC−2 were all ST11 type. Two blaNDM−5 carrying isolates were assigned to ST307 and ST1562, respectively. Conjugative assays revealed that plasmids harboring blaNDM−5 gene were self-transmissible. Plasmid analysis suggested that two blaNDM−5 were located on a 45 kb IncX3 type plasmid. The high incidence of CRKp in elderly patients with LRTIs indicates the urgent need for further surveillance and strict infection control measures.